1982
DOI: 10.1254/jjp.32.405
|View full text |Cite
|
Sign up to set email alerts
|

The central anti-serotonin activity of zotepine, a new neuroleptic, in rats.

Abstract: Abstract-2-Chloro-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
3

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
2
11
0
3
Order By: Relevance
“…In any case, zotepine had a more potent anti -serotonergic activity than clozapine, spiroperidol or oxypertine which are reported to have more potent anti-serotonergic activity than known neuroleptics or to be more anti serotonergic than anti-dopaminergic (9)(10)(11). In addition to the present results and those of our previous report (5), it is clear that zotepine has the most potent anti-sero tonergic activity of the known neuroleptics. Clozapine is reported to cause fewer extra pyramidal symptoms (9), and spiroperidol and oxypertine are reported to be effective on syndromes on which haloperidol is ineffective (12).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…In any case, zotepine had a more potent anti -serotonergic activity than clozapine, spiroperidol or oxypertine which are reported to have more potent anti-serotonergic activity than known neuroleptics or to be more anti serotonergic than anti-dopaminergic (9)(10)(11). In addition to the present results and those of our previous report (5), it is clear that zotepine has the most potent anti-sero tonergic activity of the known neuroleptics. Clozapine is reported to cause fewer extra pyramidal symptoms (9), and spiroperidol and oxypertine are reported to be effective on syndromes on which haloperidol is ineffective (12).…”
supporting
confidence: 85%
“…Fenfluramine is known to induce hyper thermia in rats by mediation of central serotonin in a warm environment (25-28'C) (5)(6)(7)(8)(9). In the present study, rats with fen fluramine-induced hyperthermia were used to investigate the anti-serotonergic activity of zotepine, and it was compared with clozapine, spiroperidol and oxypertine which are reported to have potent anti-serotonergic activity rather than anti -dopami nergic activity (9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uchida et al (1) have reported that zotepine exerts its neuroleptic effects mainly through anti-dopaminergic activity. Shimomura et al (2) have shown that zotepine is a unique neuroleptic with potent central anti serotonergic activity. L-5-hydroxytryptophan (L-5HTP), some hallucinogens and benzodi azepines can induce head-twitch in animals (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Long‐term administration of zotepine may accelerate the metabolism of dopamine and norepinephrine 6 by the feedback mechanism from the post‐receptor site to the synthesis site of dopamine and norepinephrine in the presynaptic area, due to suppressed neurotransmission by the drug. Zotepine also suppresses the central serotonin transmission system in chronic use 7 . Therefore both chronic suppression of the 5‐HT transmission system and an increased metabolism of dopamine and norepinephrine may decrease body temperature.…”
Section: Discussionmentioning
confidence: 99%